The effect of honey supplementation formula on delaying some fatigue markers on 1500 meters runners with no impact on performance - Ossama Aly, M.; Elgohary, R.; Tayel, D. I. (International Journal of Sports Science, 2019)
Background: Honey, royal jelly, and bee-pollen are promoted as nutraceuticals that have numerous nutritional and therapeutic properties with a capability of endurance athletic performance enhancement. Objective: The study aimed to evaluate the effect of honey supplementation formula on runners` performance and fatigue parameters. Subjects: Fifty male runners, members of the Egyptian Athletic Federation (EAF), were recruited to perform two study groups; one with intervention with the honey drink for one week before and after running and the second group was running without using the honey drink (placebo). Systolic and diastolic blood pressures, pulse rate, blood glucose, blood lactic acid concentration, creatine kinase-muscle/brain (CK-MB), and Lactate dehydrogenase (LDH) were measured before and after running. Results: No significant baseline intergroup differences were observed while there were significant changes were detected in both groups in all parameters investigated according to the pre-and post-exercise intragroup comparison. Blood lactic acid concentration was higher among the honey group than the placebo (19.50 ± 3.78 vs 11.0 ± 3.83 mmol/L, respectively) as well as LDH (311.30 ± 55.40 vs 242.0 ± 20.98 U/L, respectively). However, it can be explained by the insignificant faster race finishing time of the honey group than the placebo group (5.01 ± 0.24 vs 5.16 ± 0.11 minutes, respectively, (p = 0.221). The blood glucose was enormously higher among the athletes who ingested honey than who took placebo only (139.68 ± 37.76 vs 81.40 ± 7.43 mg/dl, respectively). While, there was no statistical difference in the blood pressure, either systolic or diastolic, and CK-MB between both groups. Conclusions: Acute ingestion of honey drink mixed with royal jelly and bee-pollen before running is ergogenic and plays a beneficial role in enhancing running performance.